Interaksi Edukatif Perspektif Burhanuddin az-Zarnuji - Endrisanti, Nani (Program Studi Pendidikan Agama Islam, 2022)
Educative interaction is an interaction between educators and students in the learning process. Harmonious interaction greatly influences the achievement of learning objectives. But in reality, educational interactions that are fostered today are getting less attention from educators and students. This is evidenced by the fact that some educators build bad relationships with their students, such as treating students in violent ways. So it is not surprising that students strike back. This problem is not new in the world of education but often occurs. Burhanuddin Az-Zarnuji is an Islamic education figure who examines in depth the educational interactions between educators and students. This article examines in depth Az-Zarnuji's theory of educational interaction in a number of his works concerning education, especially in his book Ta'lim Muta'alim. This research is in the form of library research using the content analysis method. The results show that Az-Zarnuji has made a major contribution in building the concept of educative interaction in Islamic education. The Az-Zarnuji concept can be used as an alternative reference to overcome the problems of educational interaction today with a new approach that is more in line with the latest developments.